(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
Iran is one of the greatest oil and gas areas. In spite of great volumes of exploitation the quantity of resources continues to increase. The incomes from natural gas and oil use and exploitation are not enough. To solve the problems must be – reducing the economic and political pressure of "super states", resolving the territorial conflicts, rational inner regional policy, increasing the volume of oil, gas and oil products export.